Foreign body in the nasopharynx- A rare entity: a Case Report - Soumik Saha; Partha Pratim Saha; Souvik Roychowdhury; Tapan Kumar Nandi (Bengal Journal of Otolaryngology and Head Neck Surgery, 2013)
Abstract